COVID‐19 as a context in suicide: early insights from Victoria, Australia - Justin Dwyer; Jeremy Dwyer; Richard Hiscock; Clare O'Callaghan; Keryn Taylor; Ciara Millar; Ashne Lamb; Lyndal Bugeja (Elsevier, 2021)
Abstract Objective: To examine how the coronavirus (COVID‐19) pandemic and its consequences may have influenced suicide in Victoria, Australia. Methods: A mixed methods study of consecutive Victorian suicide cases spanning 1 January 2015 to 31 January 2021. Interrupted time series analysis examined whether suicide frequency changed following the pandemic onset. Thematic analysis was undertaken of police reports in suicides linked with COVID‐19 to try to understand how COVID‐19 acted as a stressor. Results: The frequency of Victorian suicides did not change following the onset of COVID‐19. Sixty COVID‐linked suicides were identified, featuring three recurring themes: COVID‐19 as a disturbance in the self, in relationships with others and institutions. Conclusions: While COVID‐19 has not led to an increase in Victorian suicide frequency to date, it is an important background stressor that can erode one's wellbeing, sense of agency and connectedness to others. Implications for public health: Clinical interventions that serve to reconnect people with a sense of agency and seek to re‐establish contact with significant others are indicated. Clinicians should ensure they are familiar with pathways for their patients to access government social and economic supports. A better understanding of how government interventions may be lessening psychological distress is needed.